ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DI LAZIS JATENG CABANG SOLO - LUTFIANA, LINA; Putri, Ihwani Mukharomatul; Fajriyah, Anisa Nuril (Jurnal Riset Akuntansi Politala, 2020)
This study aims to find out the Accounting Information System at the Amil Zakat Infak and Sedekah Institute, Central Java, Solo branch. With a qualitative approach, the researcher conducted an analysis of data and information obtained from interviews and observations. The object of this study is the Accounting Information System at the Solo branch LAZIS Central Java. The results showed that the Accounting Information System at the Solo branch Lazis Central Java was processed by using the Silazisku system. With Silazisku system allows the finance department to do its work more easily. By inputting data and information in the Silazisku system the processing will be automatically carried out by the system and produce output in the form of a report that presents financial data and information. Thus the finance department does not need to do data processing by doing calculations one by one manually to make a report that presents financial data and information. This shows that the Silazisku system can improve work efficiency.